Teacher Management in Supporting the Implementation of the Merdeka Curriculum at an Elementary School - Dea Ayu Angraini (MISOOL: Jurnal Pendidikan Dasar, 2026)
The implementation of the Merdeka Curriculum requires teachers to possess effective management competencies to support the learning process. However, there is still limited research examining teacher management in the context of the Merdeka Curriculum at the elementary school level. Therefore, this study was conducted to analyze the implementation of teacher management in support of the Merdeka Curriculum at SDN 76/I Sungai Buluh, Batanghari Regency, Jambi Province. This study employed a qualitative approach with a descriptive design. The research subjects are two teachers and the principal of SDN 76/I Sungai Buluh. Data collection was conducted through observation, interviews, and documentation, and data analysis utilized an interactive model involving data collection, reduction, presentation, and drawing conclusions. The findings of this study reveal that teacher management is implemented through structured planning aligned with the Merdeka Curriculum, as well as collaboration among teachers and the school principal. Teachers’ efforts to improve the quality of learning involve carrying out various routine activities, despite the challenges they face regarding limited facilities and learning resources. In conclusion, effective teacher management plays a crucial role in supporting the successful implementation of the Merdeka Curriculum at the elementary school level and contributes to enhancing the quality of the learning process.